Establishment and Application of Engineered NIH 3T3 Cell Line with Stable Human RAGE Expression - Xinyi Xiao; Hui Chen; Pameila Paerhati; Meiqi Zhou; Zhuoyi Yang; Siyi Bai; Yunsheng Yuan (Georg Thieme Verlag KG, 2020)
Aim NIH3T3 cell line with expression of human receptor for advanced glycation end-products (hRAGE) transduced with lentivirus vectors was used to analyze affinity, biological activity, and/or molecular mechanisms of molecules targeting the hRAGE pathway. Method The DNA fragment coding for hRAGE gene was integrated into the genome of NIH3T3 cells using lentivirus transduction. Cells expressing hRAGE were selected with puromycin, and the level of hRAGE expression was analyzed by Western blot. To establish a stable cell line, colonies of hRAGE-expressing cells were generated, and the level of RAGE expression in each engineered cell line was analyzed within 20 generations. Flow cytometry assay was used to verify affinity of anti-hRAGE antibody binding to hRAGE on the surface of engineered cells. The engineered NIH3T3 cell line was applied to assess effects of anti-hRAGE blocking antibody on amyloid β-induced cells apoptosis by CCK-8 assay. Results The engineered NIH3T3 cell line (hRAGE-NIH3T3) could stably express human RAGE. Commercial anti-RAGE polyclonal antibody could recognize and bind to human RAGE on the surface of hRAGE-NIH3T3 but not original NIH3T3 cells. In addition, hRAGE-NIH3T3 was more sensitive to RAGE pathway-dependent stimulation. Our data show that the hRAGE-NIH3T3 cell line established is an excellent tool in the study of RAGE-targeting molecules based on the cellular level, biological function, and RAGE-mediated molecular mechanisms.